Potassium ferrate-containing composite particle capable of efficiently removing formaldehyde and preparation method of potassium ferrate-containing composite particle

By combining food-grade liquid silica gel and inorganic adsorption materials in the composite particles, the problems of large loss and poor stability of potassium ferrate in the preparation of composite particles are solved, and the effect of efficient formaldehyde removal is achieved.

CN119657073APending Publication Date: 2025-03-21上海乐空净健康科技有限公司
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411992439.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-03-21

AI Technical Summary

Technical Problem

In the prior art, potassium ferrate has a large loss in the preparation of composite particles, and has poor stability in the air, making it difficult to apply for a long time, and it is unable to effectively remove indoor formaldehyde.

Method used

Using composite particles containing 10-80% food-grade liquid silica gel, 1-20% potassium ferrate and 10-80% inorganic adsorbent material, the potassium ferrate is combined with liquid silica gel and inorganic adsorbent material through a specific preparation method to reduce the loss of potassium ferrate and improve its stability in the air.

Benefits of technology

It effectively reduces the loss of potassium ferrate, improves its stability in the air, extends its use time, and achieves the effect of efficient formaldehyde removal.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses potassium ferrate-containing composite particles capable of efficiently removing formaldehyde and a preparation method of the potassium ferrate-containing composite particles, and relates to the technical field of air purification. The high-efficiency formaldehyde-removing composite particle comprises potassium ferrate, food-grade liquid silica gel and an inorganic adsorption material, the food-grade liquid silica gel is used as a binder, and the potassium ferrate and the inorganic adsorption material are combined; the silica gel does not react with the potassium ferrate, so that the loss of the potassium ferrate in the preparation process is reduced; the silica gel has strong hydrophobicity, can well neutralize the characteristic of strong hygroscopicity of the potassium ferrate, and prolongs the stabilization time of the potassium ferrate in the particles in the air; the silica gel has a certain adsorption effect and can adsorb formaldehyde in the air onto the particles, so that the formaldehyde is oxidized and decomposed by utilizing the potassium ferrate in the particles. When the composite particles are used, moisture and formaldehyde in the air are adsorbed, the potassium ferrate in the particles is gradually dissolved in the water, and the formaldehyde is decomposed by utilizing the strong oxidizing property of the potassium ferrate, so that the purpose of removing the formaldehyde is achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of air purification, and in particular relates to a high-efficiency formaldehyde-removing composite particle containing potassium ferrate and a preparation method thereof. Background Art

[0002] Formaldehyde is the most common pollutant in indoor air, especially newly renovated rooms and newly purchased furniture will release more formaldehyde. Formaldehyde is very harmful to the human body. Acute exposure to high concentrations of formaldehyde may cause discomfort in the head, eyes and respiratory tract, such as tears, coughing, nausea and difficulty breathing. In addition, formaldehyde can denature proteins and nucleic acids. Long-term exposure to formaldehyde may cause cancer, childhood leukemia and premature birth.

[0003] At present, the methods for removing indoor formaldehyde mainly include photocatalytic oxidation, physical adsorption and chemical adsorption. Among them, although the photocatalytic oxidation method has strong oxidizing properties, it requires ultraviolet light and is relatively energy-consuming; the physical adsorption method is prone to adsorption saturation, and common adsorbents such as activated carbon have poor adsorption effects on low-concentration formaldehyde; the chemical adsorption method can not only adsorb formaldehyde, but also use the oxidant in the adsorbent to oxidize formaldehyde into carbon dioxide and water, and has good application prospects. The chemical adsorption method mainly uses adsorbents such as zeolite, molecular sieves and porous materials such as alumina. At present, the main method is to load strong oxidants such as potassium permanganate and sodium hypochlorite on the adsorbent by impregnation. Although these oxidants have a good effect on removing indoor formaldehyde, there are also many problems, such as potassium permanganate has a large loss during the impregnation process and the oxidizing property is not enough to completely oxidize formaldehyde, sodium hypochlorite has a pungent odor, and it will decompose chlorine under certain conditions. Therefore, it is very important to find a suitable oxidant.

[0004] Potassium ferrate is a green, environmentally friendly strong oxidant, with a standard electrode potential of 2.20V under acidic conditions and 0.7V under alkaline conditions. It is more oxidizing than common oxides potassium permanganate, potassium dichromate and sodium hypochlorite. If potassium ferrate can be combined with an adsorbent and applied to remove formaldehyde, it can not only completely oxidize indoor formaldehyde into carbon dioxide and water, but also produce no secondary pollution. However, potassium ferrate is very easy to absorb moisture in the air, and it is easy to decompose and fail, and it is difficult to use it in the air for a long time. In addition, it is also difficult to load potassium ferrate on inorganic adsorption materials in large quantities. Potassium ferrate is loaded on an adsorbent using an impregnation method. Potassium ferrate not only has a large loss, a low load, but also cannot be used in the air for a long time. Therefore, developing a composite particle containing potassium ferrate, which can reduce the loss of potassium ferrate in the preparation process, and can improve its stability in the air, and the prepared composite particles have a good removal effect on formaldehyde, is a technical problem that those skilled in the art need to solve urgently. Summary of the invention

[0005] The invention provides a highly efficient formaldehyde removal composite particle containing potassium ferrate and a preparation method thereof, which is used to solve the technical problems of large loss of potassium ferrate and poor stability in the air and difficulty in long-term application when preparing the composite particles.

[0006] In order to solve the above technical problems, the present invention is achieved through the following technical solutions:

[0007] The high-efficiency formaldehyde-removing composite particles containing potassium ferrate of the present invention comprise, by mass percentage, 10-80% of food-grade liquid silica gel, 1-20% of potassium ferrate and 10-80% of inorganic adsorption material.

[0008] Furthermore, the hardness of the liquid silicone is 15-60 degrees.

[0009] Furthermore, the particle size of the inorganic adsorption material is 10-100 mesh.

[0010] Furthermore, the inorganic adsorption material is one or more combinations of natural zeolite, activated carbon, alumina, molecular sieve and silicon dioxide.

[0011] A method for preparing a highly efficient formaldehyde removal composite particle containing potassium ferrate, which is used to prepare the highly efficient formaldehyde removal composite particle containing potassium ferrate, comprises the following steps:

[0012] S1. Take equal amounts of type A silica gel and type B silica gel in a mass ratio of 1:1, stir and mix, and prepare food-grade liquid silica gel;

[0013] S2. Mix the inorganic adsorption material and liquid silica gel in a mass ratio of 1:5-5:5 and stir evenly;

[0014] S3, adding 1-20% of potassium ferrate to the mixture of step S2 and stirring evenly, and leaving it to stand in a dry place for more than 30 minutes;

[0015] S4, using a stainless steel stripping machine, extruding the mixture obtained in step S3 into strips, and preparing it into spherical particles with a diameter of 5-15 mm through a granulation plate;

[0016] S5. Curing the prepared particles in a dry place at room temperature for more than 8 hours and storing them in a dry place.

[0017] Compared with the prior art, the present invention has the following beneficial effects:

[0018] (1) The present invention comprises potassium ferrate, food-grade liquid silica gel and inorganic adsorption material, wherein the liquid silica gel mainly acts as a binder. On the one hand, it can not only combine potassium ferrate and inorganic adsorption material, but also does not react with potassium ferrate, thereby reducing the loss of potassium ferrate during the preparation process; on the other hand, the addition of silica gel reduces the hydrophilicity of the particles, improves the stability of potassium ferrate in the air, and prolongs its use time. In addition, the hardness of the liquid silica gel needs to be greater than 15 degrees. For liquid silica gel with a hardness of more than 15 degrees, on the one hand, the content of silicon dioxide in the silica gel is higher, which is conducive to the adsorption of formaldehyde; on the other hand, the proportion of silicone oil in the silica gel is low, and the prepared particles have more pores.

[0019] (2) The potassium ferrate composite particles provided by the present invention use inorganic adsorption materials for efficiently removing formaldehyde. The inorganic adsorption materials have the following three main functions: first, the inorganic adsorption materials can adsorb formaldehyde in the air; second, the inorganic adsorption materials have a skeleton effect, which can solve the problems of the composite particles being fragile and limp; third, the mass proportion of the inorganic adsorption materials will affect the porosity of the particles. The more the mass proportion of the inorganic adsorption materials, the more porosity of the particles, which is more conducive to removing formaldehyde. However, the proportion of the inorganic adsorption materials should not be too high, as too high a proportion will lead to problems such as the particles being fragile.

[0020] (3) The potassium ferrate composite particles provided by the present invention are placed in the air to adsorb formaldehyde and part of the water vapor in the air. Part of the potassium ferrate in the particles will slowly dissolve in the water, oxidizing and decomposing the formaldehyde, thereby removing the formaldehyde.

[0021] (4) After preparation, the composite particles of the present invention should be stored at a humidity of less than 30% to prevent the particles from absorbing water and causing potassium ferrate loss during storage, thereby affecting the formaldehyde removal effect.

[0022] Of course, any product implementing the present invention does not necessarily need to achieve all of the advantages described above at the same time. DETAILED DESCRIPTION

[0023] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0024] The high-efficiency formaldehyde-removing composite particles containing potassium ferrate of the present invention include, by mass percentage, 10-80% of food-grade liquid silica gel, 1-20% of potassium ferrate and 10-80% of inorganic adsorption material; the hardness of the liquid silica gel is 15-60 degrees.

[0025] Wherein, the particle size of the inorganic adsorption material is 10-100 mesh.

[0026] The inorganic adsorption material is one or more combinations of natural zeolite, activated carbon, alumina, molecular sieve and silicon dioxide.

[0027] A method for preparing a highly efficient formaldehyde removal composite particle containing potassium ferrate, which is used to prepare the highly efficient formaldehyde removal composite particle containing potassium ferrate, comprises the following steps:

[0028] S1. Take equal amounts of type A silica gel and type B silica gel in a mass ratio of 1:1, stir and mix, and prepare food-grade liquid silica gel;

[0029] S2. Mix the inorganic adsorption material and liquid silica gel in a mass ratio of 1:5-5:5 and stir evenly;

[0030] S3, adding 1-20% of potassium ferrate to the mixture of step S2 and stirring evenly, and leaving it to stand in a dry place for more than 30 minutes;

[0031] S4, using a stainless steel stripping machine, extruding the mixture obtained in step S2 into strips, and preparing it into spherical particles with a diameter of 5-15 mm through a granulation plate;

[0032] S5. Curing the prepared particles in a dry place at room temperature for more than 8 hours and storing them in a dry place.

[0033] Embodiment 1:

[0034] The mass ratio of food grade liquid silica gel and 40 mesh zeolite is 5:4;

[0035] The actual content of potassium ferrate in the granules is 6%;

[0036] Food grade liquid silicone with a degree of 30 degrees.

[0037] Embodiment 2;

[0038] The mass ratio of food grade liquid silica gel and 40 mesh zeolite is 5:3;

[0039] The actual content of potassium ferrate in the granules is 8%;

[0040] Food grade liquid silicone with a degree of 30 degrees.

[0041] Embodiment 3:

[0042] The mass ratio of food grade liquid silica gel and 40 mesh zeolite is 5:5;

[0043] The actual content of potassium ferrate in the granules is 15%;

[0044] Food grade liquid silicone with a degree of 30 degrees.

[0045] Comparative Example 1:

[0046] The mass ratio of food grade liquid silica gel and 40 mesh activated carbon is 5:4;

[0047] The actual content of potassium ferrate in the granules is 6%;

[0048] Food grade liquid silicone with a degree of 30 degrees.

[0049] Comparative Example 2:

[0050] The mass ratio of food grade liquid silica gel and 40 mesh activated carbon is 5:2;

[0051] The actual content of potassium ferrate in the granules is 8%;

[0052] Food grade liquid silicone with a degree of 30 degrees.

[0053] Comparative Example 3:

[0054] The mass ratio of food grade liquid silica gel and 40 mesh activated carbon is 5:4;

[0055] The actual content of potassium ferrate in the granules is 15%;

[0056] Food grade liquid silicone has a temperature of 0 degrees.

[0057] Comparative Example 4:

[0058] The mass ratio of food grade liquid silica gel to 40 mesh zeolite is 5:2;

[0059] The actual content of potassium ferrate in the granules is 6%;

[0060] Food grade liquid silicone with a degree of 30 degrees.

[0061] Comparative Example 5:

[0062] The mass ratio of food grade liquid silica gel and 40 mesh zeolite is 5:5;

[0063] The actual content of potassium ferrate in the granules is 8%;

[0064] Food grade liquid silicone has a temperature of 0 degrees.

[0065] Effect test example

[0066] 1. Loss of potassium ferrate in composite particles

[0067] The potassium ferrate content in the particles was determined by the chromite method.

[0068] sample Theoretical content of potassium ferrate / % Actual content of potassium ferrate / % Potassium ferrate loss / % Example 1 6.00 5.05 15.83 Example 2 8.00 7.10 11.25 Example 3 15.00 13.00 13.33 Comparative Example 1 6.00 3.55 40.83 Comparative Example 2 8.00 4.58 42.75 Comparative Example 3 15.00 8.05 46.33 Comparative Example 4 6.00 5.22 13.00 Comparative Example 5 8.00 7.15 10.63

[0069] It can be seen from the above results that, in the samples of Examples 1-3 and Comparative Examples 4-5, 40-mesh zeolite was used as the inorganic adsorption material, and the potassium ferrate loss in the composite particles after preparation was as low as 10.63% and as high as 15.83%. When 40-mesh activated carbon was used as the inorganic adsorption material in the samples of Comparative Examples 1-3, the potassium ferrate loss in the particles after preparation was greater than 40%, and the maximum loss was 46.33%. This is mainly because even under dry conditions, activated carbon will react with potassium ferrate, resulting in a large loss of potassium ferrate. It can be seen that the inorganic adsorption material selected when preparing the composite particles should preferably be a material that does not react with potassium ferrate, so that the loss of potassium ferrate is as small as possible.

[0070] 2. Formaldehyde removal effect

[0071] In a 10L experimental chamber, 10g of formaldehyde removal sample containing potassium ferrate was placed. Under a certain formaldehyde concentration, the fan was turned on for 1 hour, the formaldehyde concentration was measured, and the removal rate was calculated.

[0072] sample <![CDATA[Initial formaldehyde concentration / mg·m -3 > <![CDATA[Formaldehyde concentration after 1 h / mg·m -3 > Removal rate / % Example 1 0.6 0.05 91.67 Example 2 0.8 0.08 90.00 Example 3 1.0 0.07 93.00 Comparative Example 1 0.6 0.05 91.67 Comparative Example 2 0.8 0.14 82.50 Comparative Example 3 1.0 0.18 82.00 Comparative Example 4 0.6 0.11 81.67 Comparative Example 5 0.8 0.14 82.50

[0073] It can be seen from the above results that the formaldehyde removal rates of Examples 1-3 and Comparative Example 1 samples within 1 hour are all higher than 90%, and the highest removal rate is 93.00%. The formaldehyde removal rates of Comparative Examples 2-5 samples within 1 hour are all around 82%. Among them, in Comparative Examples 2 and 4 samples, the proportion of inorganic adsorption materials decreases, resulting in a decrease in pores and a decrease in the adsorption effect of particles on formaldehyde. The formaldehyde removal rates within 1 hour are only 82.50% and 81.67%. In Comparative Examples 3 and 5 samples, the hardness of silica gel is 0 degrees, and the formaldehyde removal rates within 1 hour are 82.00% and 82.50%, respectively. The main factor affecting the hardness of silica gel is the ratio of silicone oil and silicon dioxide in its components. The lower the hardness, the higher the silicone oil content, resulting in insufficient pores in the prepared particles and a decrease in the formaldehyde removal effect.

[0074] The preferred embodiments of the present invention disclosed above are only used to help illustrate the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to the specific implementation methods described. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.

Claims

1. A highly efficient formaldehyde removal composite particle comprising potassium ferrate, characterized in that: According to mass percentage, it includes 10-80% of food-grade liquid silica gel, 1-20% of potassium ferrate and 10-80% of inorganic adsorption material.

2. The high-efficiency formaldehyde-removing composite particle containing potassium ferrate according to claim 1, characterized in that: The hardness of the liquid silicone is 15-60 degrees.

3. The high-efficiency formaldehyde-removing composite particle containing potassium ferrate according to claim 1, characterized in that: The particle size of the inorganic adsorption material is 10-100 meshes.

4. The high-efficiency formaldehyde-removing composite particle containing potassium ferrate according to claim 2, characterized in that: The inorganic adsorption material is one or more combinations of natural zeolite, activated carbon, alumina, molecular sieve and silicon dioxide.

5. A method for preparing a highly efficient formaldehyde removal composite particle containing potassium ferrate, which is used to prepare a highly efficient formaldehyde removal composite particle containing potassium ferrate as claimed in any one of claims 1 to 4, characterized in that: The steps include: S1. Take equal amounts of type A silica gel and type B silica gel in a mass ratio of 1:1, stir and mix, and prepare food-grade liquid silica gel; S2. Mix the inorganic adsorption material and liquid silica gel in a mass ratio of 1:5-5:5 and stir evenly; S3, adding 1-20% of potassium ferrate to the mixture of step S2 and stirring evenly, and leaving it to stand in a dry place for more than 30 minutes; S4, using a stainless steel stripping machine, extruding the mixture obtained in step S3 into strips, and preparing it into spherical particles with a diameter of 5-15 mm through a granulation plate; S5. Curing the prepared particles in a dry place at room temperature for more than 8 hours and storing them in a dry place.